High temperature oxidation resistance of (Ti, Ta)(C, N)-based cermets. (January 2016) - Chicardi, E.; Córdoba, J.M.; Gotor, F.J.
Highlights: Cermets based on (Ti, Ta)(C, N) were oxidized in air between 800 and 1100 °C for 48 h. The substitution of Ti by Ta resulted in a high resistance to oxidation. A protective layer of cobalt titanates at the surface of cermets was observed. A rutile phase in which some Ti 4+ are replaced by Ta 5+ was detected. This replacement decelerated the oxygen diffusion into the cermets. Abstract: Cermets based on titanium–tantalum carbonitride were oxidized in static air between 800 °C and 1100 °C for 48 h. The thermogravimetric and microstructural study showed an outstanding reduction in the oxidation of more than 90% when the Ta content was increased. In cermets with low Ta content, the formation of a thin CoO/Co3 O4 outer layer tends to disappear by reacting with the underlying rutile phase, which emerges at the surface. However, in cermets with higher Ta content, the formation of an external titanate layer, observed even at a low temperature, appears to prevent the oxygen diffusion and the oxidation progression.